PEMBENAHAN TERHADAP LEMBAGA PEMASYARAKATAN DAPAT MENIADAKAN OPSI HUKUMAN MATI BAGI NARAPIDANA DI INDONESIA (THE IMPROVEMENT OF QUALITY OF PENITENTIARY CAN ELIMINATE THE DEATH PENALTY OPTIONS OF CONVICTED CRIMINALS IN INDONESIA) - Nomensen Freddy Siahaan (Law Department, University of Widya Gama Mahakam Samarinda, 2018)
After a long time was not heard to the public area, lately death penalty toward the criminal cases that classified as extraordinary crime are appear. The author discovers electronic article about the execution of the death penalty which is the prosecutor prepares to execute death penalty toward the drugs dealer. The president of Republic of Indonesia stated that it is necessary to give a deterrent effect to the convicted criminal and keep the morality of Indonesian teenagers. According to my opinion, the author argues that it will be better and wiser if we discuss about renovating all of the Penitentiary in Indonesia than debating whether death penalty could be done in Indonesia or not, because it will be displeasure many parties, death penalty infringed the human rights of the convicted criminals and cause psychological burden to them, families, the executor of the death penalty, and other parties. Because if we have to improve the quality of the Penitentiary, if the function of Penitentiary for fostering moralily has been optimal or properly enough to the convicted criminals, Indonesia will be no longer need the death penalty option as sanction to the convicted crimanals including for the extraordinary crime (especially for drugs trafficking in our country). Penitentiary is one of the public services which aims for fostering the people that initially have bad habits (commited to the crime), so that they will have the awareness to change their bad attitude into the be better ones, will not harm others, and positively contributed to the society. Already Penitentiary’s conditions should be designed in such a way and as good as possible, so that the inmates feels like at their own home (like having a second home after his own home), and feel humaner to spend their days in the Penitentiary. The author believes that if the Penitentiary has been improved and optimized its function well, then the real purpose of Penitentiary will definitely achieved. As stated in Law Number 12 Year 1995 regarding to Penitentiary Article 2 which states